DEOXYRIBONUCLEASE (DNAse) DAN INHIBITOR DNAse - Rambe, Ismatul Fauziah; Yamamoto, Zulham (Buletin Farmatera, 2022)
Deoxyribonuclease (DNAse) is an enzyme that plays an important role in cell apoptosis and has the function of hydrolyzing DNA. There are two types of DNAse, namely i) DNAse I which works well at neutral pH (6.5-8.0) and requires bivalent ions such as magnesium (Mg2+) and calcium (Ca2+) for activation, and ii) DNAse II which works by good at acidic pH and does not require bivalent ions. DNAse inhibitors are required to control the activity of DNAse. Both DNAse and its inhibitors have a role in the pathogenesis of various diseases, such as in the autoimmune disease systemic lupus erythematosus. DNase inhibitors can be obtained from natural, conventional, or chemical sources.